Peran Strategis Pendidikan Islam dalam Mencapai Tujuan Pembangunan Berkelanjutan (SDGs) di Indonesia: Systematic Literature Review - Sari, Indah; Fahmi, Muhammad Nabil; Faqihuddin, Achmad (Universitas Pendidikan Indonesia, 2025)
AbstractIslamic Religious Education (PAI) tends to be overlooked in global discussions on achieving the Sustainable Development Goals (SDGs). So far, Islamic involvement in SDG initiatives has mostly focused on economics, philanthropy, and religious moderation. Yet, normatively and historically, PAI holds significant potential to internalize sustainable development values based on Islamic principles. This study employs a Systematic Literature Review (SLR) method to map current trends in the contributions of PAI toward achieving the SDGs. The literature analyzed comprises journal articles published within the last five years in either Indonesian or English and specifically discusses PAI's role in supporting SDG objectives. The findings reveal that integrating Islamic values into curricula, applying contextual learning approaches, and promoting character building, tolerance, and social responsibility are key contributions of PAI in creating inclusive and sustainable education. This study recommends the systematic integration of Islamic values in PAI to strengthen education’s role in supporting the achievement of quality SDG-aligned education.Keywords: Islamic Religious Education, Sustainable Development, Inclusive Curriculum, Islamic Values, Social ResponsibilityAbstrakPendidikan Agama Islam (PAI) cenderung terabaikan dalam diskursus global tentang pencapaian Sustainable Development Goals (SDGs). Selama ini, pelibatan Islam dalam proyek SDGs lebih banyak terbatas pada aspek ekonomi, filantropi, dan moderasi beragama. Padahal, secara normatif dan historis, PAI memiliki potensi signifikan dalam menginternalisasikan nilai pembangunan berkelanjutan berbasis Islam. Penelitian ini menggunakan metode Systematic Literature Review (SLR) untuk memetakan tren terkini mengenai kontribusi PAI dalam mendukung pencapaian SDGs. Literatur yang dianalisis adalah artikel jurnal terbit lima tahun terakhir yang relevan dan berbahasa Indonesia atau Inggris. Hasilnya menunjukkan bahwa integrasi nilai-nilai Islam dalam kurikulum, pendekatan pembelajaran kontekstual, serta penguatan karakter, toleransi, dan tanggung jawab sosial menjadi kontribusi nyata PAI dalam menciptakan pendidikan yang inklusif dan berkelanjutan. Penelitian ini merekomendasikan integrasi sistematis nilai-nilai Islam dalam PAI guna memperkuat peran pendidikan dalam pencapaian SDGs, khususnya tujuan pendidikan berkualitas. Kata kunci : Pendidikan Agama Islam, Pembangunan Berkelanjutan, Kurikulum Inklusif, Nilai-Nilai Islam, Tanggung Jawab Sosial